Intrinsic artefacts in optical oxygen sensors--how reliable are our measurements? - Lehner,P; Staudinger,C; Borisov,SM; Regensburger,J; Klimant,I (Chemistry, 2015)
Optical oxygen sensing is of broad interest in many areas of research, such as medicine, food processing, and micro- and marine biology. The operation principle of optical oxygen sensors is well established and these sensors are routinely employed in lab and field experiments. Ultratrace oxygen sensors, which enable measurements in the sub-nanomolar region (dissolved oxygen), are becoming increasingly important. Such sensors prominently exhibit phenomena that complicate calibration and measurements. However, these phenomena are not constrained to ultratrace sensors; rather, these effects are inherent to the way optical oxygen sensors work and may influence any optical oxygen measurement when certain conditions are met. This scenario is especially true for applications that deal with high-excitation light intensities, such as microscopy and microfluidic applications. Herein, we present various effects that we could observe in our studies with ultratrace oxygen sensors and discuss the reasons for their appearance, the mechanism by which they influence measurements, and how to best reduce their impact. The phenomena discussed are oxygen photoconsumption in the sensor material; depletion of the dye ground state by high-excitation photon-flux values, which can compromise both intensity and ratiometric-based measurements; triplet-triplet annihilation; and singlet-oxygen accumulation, which affects measurements at very low oxygen concentrations.